THE ROLE OF VITAMIN D IN THE INCIDENCE OF METABOLIC SYNDROME IN UNDERGRADUATE FEMALE STUDENTS IN SAUDI ARABIA (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Background: Vitamin D insufficiency/deficiency prevalent in all age groups across the world is common in obesity and may play an important role in the risk factors of metabolic syndrome (MS).  Objectives: This cross-sectional study is to evaluate the  relationship  between  levels  of  adiponectin  and  circulating  25(OH)D,  and  its  effect  on  metabolic  biomarker  among overweight/obese female students.  Methods: Three hundred female students; with mean age 20.9 ± 3.2 years were attending the Aljouf  University, Sakaka, Saudi Arabia. They were randomly selected from university during the studying year 2015 – 2016. Anthropometric and biochemical indices were determined. Results: The study showed 19% of the female’s student were either overweight or obese (15% and 4%, respectively). The frequency of MS diagnosis among the students was 17%, with 13% and 4% had  either  three  or four  risk factors,  respectively.  Overweight/obese  subjects  had  significantly  worse  anthropometric  and biochemical characteristics, including waist/hip ratio, blood pressure (BP), fasting blood glucose (BG), insulin, insulin resistance (HOMA-IR), triglyceride levels (TG), low-density lipoprotein cholesterol levels (LDL-C), leptin, adiponectin, leptin/adiponectin ratio and high-density lipoprotein cholesterol levels (HDL-C) compared to normal weight. Of the subjects diagnosed with MS, 59% had mild and 8.6% had severe 25(OH)D deficiency. There was negative association between 25(OH)D and both FBG and HOMA-IR among young women  obese/overweight.  Conclusion: In  our study,  it suggested that low  level of  adiponectin was strongly correlated with low 25(OH)D levels. Also, the prevalence of MS tends to increase with high occurrence rate of low circulating 25(OH)D levels that is, known cause poor glycemic control and prediction of cardiovascular outcomes.